Thermal-elastic fracture analysis of composites with defects - Guo, Jun Yan. (2008)
The interaction of micro-cracks or voids with inhomogeneities is an important topic in studying the strength and fracture toughness of materials. A lot of contributions have been made to investigate this phenomenon in the past few decades.